An evaluation of the combination effect of zoledronate and chemotherapeutic agents in canine osteosarcoma cells - Iwaki, Yoshimi; Lindley, Stephanie E. S.; Bergman, Noelle; Smith, Bruce F.; Pondugula, Satyanarayana R. (Frontiers in Veterinary Science, 2024)
Osteosarcoma (OSA) is an aggressive form of bone cancer in both dogs and humans. The treatment options for metastatic (stage III) OSA are currently limited and the prognosis is poor. Zoledronate, a second generation amino-bisphosphonate, is commonly used for palliation of cancer induced bone pain. Zoledronate has also demonstrated anti-cancer properties and possibly enhances the cytotoxicity of doxorubicin in a canine histiocytosis cell line and human prostatic cancer cell line. The goal of this study was to evaluate the combination effect of zoledronate and various chemotherapeutic drugs in canine OSA cells. Canine OSA cell line (D17), cells from two canine primary OSAs, and MDCK, a canine kidney cell line, were used to evaluate the therapeutic potential of these drugs. Carboplatin, doxorubicin, vinorelbine, toceranib, and isophosphoramide mustard (active metabolite of ifosfamide) were used as chemotherapeutic agents. First, cells were treated with either zoledronate or chemotherapy drug alone for 72 hours. Cell viability was assessed using CellTiter Glo and IC5, IC10, IC20, and IC50 were calculated. Second, cells were treated with a combination of zoledronate and each chemotherapeutic agent at their IC5, IC10, IC20, and IC50 concentrations. After 72 hours, cell viability was assessed by CellTiter Glo. Zoledronate, carboplatin, doxorubicin, vinorelbine, and isophosphoramide mustard showed concentration dependent decrease in cell viability. Toceranib showed decreased cell viability only at higher concentrations. When zoledronate was used in combination with chemotherapy drugs, while it showed potential synergistic effects with toceranib, potential antagonistic effects with vinorelbine and isophosphoramide mustard were observed. However, the results differed by cell line and thus, further evaluation is warranted to understand the exact mechanism of action.